Eliciting Mathematical Thinking of Students through Realistic Mathematics Eucation - Anwar, Lathiful; Budayasa, I Ketut; Amin, Siti Maghfirotun; Haan, Dede de (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2012)
This paper focuses on an implementation a sequence of instructional activities about addition of fractionsÃ‚Â that has been developed and implemented in grade four of primary school in Surabaya, Indonesia. The theory of Realistic Mathematics Education (RME) has been applied inÃ‚Â theÃ‚Â sequence, which aims to assist low attaining learners in supporting studentsÃ¢â‚¬â„¢ thinking in the addition of fractions. Based on the premise that eliciting and addressing learnersÃ¢â‚¬â„¢ alternative conceptions in mathematics is beneficial inÃ‚Â assisting them to improve their understanding, the paper seeks to explore the role that RME plays pertaining to this particular supposition. The paper presents and discusses examples of learnersÃ¢â‚¬â„¢ responses to contextual problems given to them during the course of the instructional activities. Keywords: Realistic Mathematics Education, mathematical thinking, a sequence of instructional activitiesÃ‚Â DOI: http://dx.doi.org/10.22342/jme.3.1.620.55-70